Prospective study on antibiotic prescription in South Indian pediatric population – a pediatrician’s and parent’s perspective - Dinesh, K.; Rangasamy, K.; Sreenivasan, V. (Creative Pharma Assent, 2023)
Background: Soaring rates of antibiotic prescriptions to children have led to antibiotic resistance in the community. Thus, prescribing, dispensing, administering, and using medication needs special attention in the current scenario. Objectives: To study the pattern and rationality of antibiotic use in pediatric patients (1 month to 18 years of age) by using the patient records & prescription and to assess parents' awareness of treatment received and antibiotic awareness by using a questionnaire. Materials and Methods: It was a Prospective study performed at Pediatric OPD of Vinayaka Missions Kirupananda Variyar Medical College and Hospital for 6 months wherein a total of 1200 paediatric OPD and IPD patients were included. The patient’s/caretaker’s adequacy of each parameter was given a Score of 1 and a Score of 0 for inadequacy. Based on these seven parameters, each patient was given a Score of a minimum of 0 to a maximum of 7. Results: The patients included Neonates (6%), infants (8%), children (56%) and adolescents (30%). Results showed that 58% of male patients were majorly affected than female pediatric individuals (42%). The use of antibiotics was observed only in 14 out of 1200 prescriptions. Among the antibiotics, cefotaxime was the most frequently prescribed medication. As per the sum of scores obtained by the patients, 492 (42%) of 1200 patients understood their drug use parameters moderately, followed by well-understood 408 (34%) and poorly understood 300 (24%). Conclusion: This study highlights the rational use of antibiotics among patients and healthcare professionals, thus paving the way to minimize antibiotic resistance.